(untitled) (Research, Society and Development, 2022)
Azadirachta indica A. Juss. (Meliaceae) is a plant whose leaves present several pharmacological activities, among them: antioxidant, antimicrobial and hypoglycemic. The present work aims to determine and validate a spectrophotometric analytical method for quantification of total flavonoids, expressed as rutin, in A. indica leaves and to optimize the extraction conditions of these flavonoids. For the selection of the spectrophotometric method, four analytical methods were investigated. The method selected as the most efficient, simple, fast and sustainable has been validated and optimized. The validation was performed according to criteria of national and international regulatory agencies. Box Behnken design (33) and the response surface methodology (RSM) were used to estimate the best extraction conditions. The analytical method that met the study criteria consisted of ultrasound-assisted extraction (UAE) of the plant material in hydroethanolic solution, at a temperature of 60 ºC, for 30 minutes, followed by filtration, dilution of the extract in ethanol/0.02 M acetic acid solution (99:1) and absorbance reading in a spectrophotometer at 364nm. In the validation stages, this method was shown to be linear (linear interval - 20 to 80 μg/mL), precise (intraday and interday), accurate (mean recovery of 120.8%), robust and selective (absence of matrix effect). The best conditions for the UAE process were: Ethanol content 30% (p/p), plant material/solvent ratio 0.2 g/mL and extraction time of 33 minutes. The spectrophotometric method and the UAE conditions determined in this study are suitable for use in the quality control of plant drugs and ethanol extracts from the leaves of Azadirachta indica.